Estimation of the Ventilation Transit Time Distribution at the Yap−Mariana Junction Using 39Ar, 85Kr and 14C Tracers. Issue 7 (28th June 2022) - Gu, Ji‐Qiang; Jiang, Wei; Tong, Amin L.; Yang, Guo‐Min; Dong, Xi‐Ze; Ritterbusch, Florian; Wang, Fan; Wang, Jianing
Abstract: We report on a multi‐tracer study at the Yap‐Mariana Junction in the western Pacific using three tracers— 85 Kr, 39 Ar, and 14 C—with different half‐lives and source functions to the oceans. The vertical profiles of 85 Kr and 39 Ar are measured using the state‐of‐the‐art Atom Trap Trace Analysis method. This method allows analysis of 85 Kr and 39 Ar isotopes with samples collected in regular Niskin bottles. Combined with the calculated natural 14 C data, we infer the ventilation transit‐time distribution (TTD) at the Yap‐Mariana Junction. The mean ages of the seawater below the thermocline at the Yap‐Mariana Junction are over 1, 000 years. Moreover earlier 39 Ar and natural 14 C data collected in other parts of the Pacific are used to infer the local TTDs and compared with the one at the Yap‐Mariana Junction. The age spectra of the Pacific bottom waters show progressive changes and increasing tails of the old water along the route from south to north. The dominance of the North Pacific Deep Water (NPDW) in the North Pacific and the effect of mixing between old water masses and younger ones at the Yap‐Mariana Junction are reflected from the different shapes of the TTDs at these locations. The TTD shows the oldest water exists at about 2, 000 m depth in the North Pacific. The western Pacific shows the highest degree of mixing at 1, 000 m depth, while the southern Pacific has the highest degree of mixing close to the bottom. Plain Language Summary: Tracers with different time responses are versatile tools for studying ventilation and mixing processes in the ocean. We conducted a multi‐tracer study at the Yap‐Mariana Junction in the western Pacific using 85 Kr, 39 Ar, and 14 C. The tracer data are used to constrain the ventilation time at this location and show that the mean ages of the seawater below the thermocline are over 1, 000 years. The local ventilation time differs significantly from the ones determined at other locations across the Pacific Ocean. Key Points: Atom trap trace analyses of 39 Ar and 85 Kr combined with 14 C constrain ventilation transit time distributions (TTD) at the Yap‐Mariana Junction The ventilation TTDs at the deep Pacific have similar mean ages but different Δ/Γ ratios The mean ages of the seawater below the thermocline at the Yap−Mariana Junction are over 1000 years with Δ/Γ ratios around 1